TRADISI PENYALINAN NASKAH ISLAM PALEMBANG: Ditinjau dari perspektif Ekonomi - Nyimas Umi Kalsum (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2013)
Abstract: Why the lease on the script? The manuscript is one of the sources of knowledge that contains a variety of data, information, thoughts, feelings and knowledge of the history and culture of a particular nation or social group. It was written by a variety of literacy and local languages was produced. So many manuscripts scattered in the archipelago, but the study of this text can be said to be rare; this is caused by the use of language and script in a script that is difficult to understand. Therefore there should be a special review on this field. In general, the study of manuscripts made with emphasis on the comparison of the content of the text in terms of content. This paper does not discuss the content of the text as a whole, but merely reviewing the manuscript kodikologi aspects that are still not widely applied. This is done to know the history of the writing of various literary events nationwide especially on copying the manuscript tradition of Islam in Palembang. Through scriptorium / studio writing writing activities, writing traits and other activities that are part of the cultural history of a region. So the economic perspective will be seen here through reading kolopon available on the manuscript. Keywords: Manuscrift, penyalinan, sewa dan ekonomi..